Investigation of 3d-printed samples for proton radiotherapy application; Innovative Technologies of Nuclear Medicine and Radiation Diagnostics and Therapy - Chernova O. S. Olga Sergeevna; Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Saburov V. I. Vladimir Leonidovich; Stuchebrov S. G. Sergey Gennadevich (2022, 2022)
Title screen